Feminist theory: The intellectual traditions of American feminism - Donovan, Josephine (Frederick Ungar Publ, 1985)
Cette première grande étude de la théorie féministe aborde la question fondamentale, "Qu'est-ce que le féminisme?" en esquissant les différents courants de la théorie féministe: libérale, culturelle, marxiste-socialiste, freudienne et radicale.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; fem9000; féminisme marxiste; féminisme radical; patriarcat; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Margaret Thatcher is my sister: Counselling on divisions between women - Itzin, Catherine (Women's Studies International Forum, 1985)
This paper looks at the ways in which women are divided from themselves and each other as women: at the internalised oppression which results from THE oppression of patriarchy, at the systematic mistreatment of women as a group by men as a group reinforced by the social structures of male power. It also looks at the ways in which women are divided from each other as a result of other oppressive systems such as class and/or race or religion or physical ability or age. The paper then describes how the particular theory and practice of Re-evaluation Counselling can be used to ‘deconstruct’ or ‘discharge’ the internalised oppression of patriarchy and other oppressive systems, making the principles of Women's Liberation and sisterhood a practical possibility for ‘everywoman’ and all women—including Margaret Thatcher. Throughout, the word ‘patriarchy’ is used to mean the system of male power usually regarded as synonymous with sexism.
Keywords: approches et analyses; capacitisme; militance; patriarcat; racisme; sororité; systèmes d'oppressions; thématiques; âgisme

Les lesbiennes et le féminisme - Roy, Carolle (Collection Femme, 1985)
Keywords: 1900-1999; 1970-1979; 1980-1989; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; patriarcat; premiers peuples; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques